2022
DOI: 10.3390/biomedicines10102337
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Actions of Polyphenols from Red and White Grape Pomace in Ischemic Heart Diseases

Abstract: Grape pomace (GP) represents a very reliable source of polyphenols because it could be found globally as a remnant of the wine industry. During the winemaking process, two types of GP are generated: red GP and white GP, according to the produced wine, red or white. Grape pomace represents a viable source of polyphenols, mainly flavanols, procyanidins anthocyanins, and resveratrol which possess antioxidant and anti-inflammatory activities. Multiple differences were observed between red and white GP in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 87 publications
0
12
0
3
Order By: Relevance
“…Grapes are among the richest and most diverse sources of phenolic compounds in the plant kingdom, which can be used in various foods, cosmetics, and pharmaceutical products [ 1 , 2 , 3 ]. The processing of grapes into wine or juices generates a large number of by-products, such as grape pomace (GP), which is a potential feedstock for biorefineries for the sustainable production of biofuels and biobased products (chemicals, materials, biopolymers, food, feed, pharmaceuticals, nutraceuticals) due to its chemical composition (proteins, fats, sugars, fibers, polyphenols, minerals, vitamins, fatty acids, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grapes are among the richest and most diverse sources of phenolic compounds in the plant kingdom, which can be used in various foods, cosmetics, and pharmaceutical products [ 1 , 2 , 3 ]. The processing of grapes into wine or juices generates a large number of by-products, such as grape pomace (GP), which is a potential feedstock for biorefineries for the sustainable production of biofuels and biobased products (chemicals, materials, biopolymers, food, feed, pharmaceuticals, nutraceuticals) due to its chemical composition (proteins, fats, sugars, fibers, polyphenols, minerals, vitamins, fatty acids, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The effective utilization of food industry residues, including GP to recover phenolic compounds and produce various other value-added products, is increasingly being considered a sustainable waste management strategy. The valorization of by-products is of great interest for tackling the problems arising from the disposal of GP and for achieving the goals of the circular bioeconomy [ 1 , 5 , 6 ]. Phenolic compounds found in GP can be divided into: flavonoids (flavanols, flavonols, anthocyanins, isoflavones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso del orujo de uva blanca se destaca el gran contenido de ácidos fenólicos como vanílico (11.5 μg/g), gentísico (29.4 μg/g), siríngico (14 μg/g), ferúlico (5.76 μg/g), entre otros; además de catequinas (68.7 μg/g) [15] y otros flavonoides como rutina (2.63 μg/g), quercetina (6.69 μg/g), luteolina (3.50 μg/g), etc. [10], [16]. Otros compuestos incluyen, ácidos caftárico, clorogénico y coutárico, y flavonoides como kaempferol, astilbina y engelitina [11].…”
Section: Orujo Como Fuente De Compuestos Fenólicosunclassified
“…El orujo de uva es resultado del prensado de uvas en la elaboración de vino blanco o tras la etapa de fermentación en el caso del vino tinto [6] y consta principalmente de la piel o cáscara, pulpa residual, semillas y tallos [5], [8], [9]. Aunque sea considerado como un residuo o desperdicio, usualmente el aprovechamiento que se le da a esta materia es como abono para los cultivos (de uva) o como alimento para animales [3], [10]. La idea de darle un valor agregado a este subproducto tiene ya más de 40 años [9].…”
Section: Introductionunclassified
“…In particular, accumulating studies have shown that the improvement of aging-related chronic diseases such as neurodegenerative, cardiovascular, and ocular diseases by anthocyanins is closely associated with their potent antioxidant action [ 3 , 6 , 7 ]. The antioxidant potency of anthocyanins is primarily related to increased reactive oxygen species (ROS) scavenging capacity through regulation of antioxidant-related signaling pathways [ 8 - 10 ]. For example, the alleviation of insulin resistance, inflammation and tissue damage by anthocyanins isolated from Aronia melanocarpa (Michx.)…”
Section: Introductionmentioning
confidence: 99%